Total Glucosides of Paeony (TGP) Inhibits Macrophages Infiltration and NLRP3-Mediated Inflammatory Response in Acute Gouty Arthritis Mice - Liu J; Liu G; Chu T; Wu Y; Yan X; Pang L; Fang W (Journal of Inflammation Research, 2025)
Jing Liu,1 Ge Liu,1 Teng Chu,1 Yue Wu,1 Xingyu Yan,1 Liping Pang,2 Weirong Fang1 1School of Basic Medicine and Clinical Pharmacy, China Pharmaceutical University, Nanjing, Jiangsu, People’s Republic of China; 2Department of Medicine, Ningbo Liwah Pharmaceutical Co., Ltd, Ningbo, Zhejiang, People’s Republic of ChinaCorrespondence: Weirong Fang, School of Basic Medicine and Clinical Pharmacy, China Pharmaceutical University, Nanjing, Jiangsu, People’s Republic of China, Email weirongfang@cpu.edu.cnPurpose: The cascade of inflammation caused by the activation of NLRP3 inflammasome plays an important role in monosodium urate (MSU)-induced acute gouty arthritis (AGA) in mice. This study aimed to evaluate the therapeutic effect of total glucosides of paeony (TGP) in AGA mice and elucidate the underlying anti-inflammatory mechanism.Materials and Methods: MSU crystals were injected into the ankle joint to establish the AGA model in mice, and bone marrow-derived macrophages (BMDMs) were primary cultured and stimulated with MSU and LPS to model inflammatory conditions in vitro. Ankle diameter was measured to quantify joint swelling. Pain was assessed by the fifty percent paw withdrawal threshold (PWT) test and the bipedal support test. Pro-inflammatory cytokine levels and arthropathological damage were analyzed by ELISA, H&E staining, and immunohistochemistry staining. The mRNA and protein expression of NLRP3 inflammasome-associated signaling pathways were determined by RT-qPCR and Western blotting, respectively. Mitochondrial oxidative damage was evaluated using flow cytometry and immunofluorescence staining.Results: Four-week TGP administration with 360, 540, 720 mg/kg respectively significantly attenuated joint swelling and pain (P < 0.05, P< 0.01), reduced pro-inflammatory cytokine secretion (P < 0.01), and ameliorated joint pathology and macrophage infiltration (P < 0.01) in AGA mice. In BMDMs, TGP (30, 60 μg/mL) treatment notably suppressed mRNA and protein expression of NLRP3, caspase-1, and IL-1β, and lowered inflammatory factor secretion (P < 0.05, P< 0.01). Additionally, cellular and mitochondrial ROS levels were both significantly decreased (P < 0.01), while ATP concentration markedly increased (P < 0.01), suggesting improved mitochondrial function.Conclusion: TGP significantly alleviated experimental AGA by reducing macrophage infiltration and suppressing the NLRP3-mediated inflammatory response.Keywords: acute gouty arthritis, total glucosides of paeony, inflammatory response, NLRP3, monosodium urate, macrophage